Полиаденилирование про-мРНК. 1 . Образование З'-концов мРНК позвоночных - Зарудная, М.И. (Біополімери і клітина, 2001)
В обзоре изложены современные представления о процессе образования 3'-концов мРНК позвоночных: охарактеризованы участвующие в реакции белки и сигнальные последовательности про-мРНК, направляющие реакцию, описан процесс сборки комплекса полиаденилирования, обсуждена связь между полиаденилированием и процессами транскрипции и сплайсинга, приведены примеры регуляции реакции образования 3'-концов мРНК В огляді докладно розглянуто процес утворення 3'-кінців мРНК хребетних: охарактеризовано білки, які беруть участь у реакції, та сигнальні елементи, що її направляють; описано процесе складання комплексу поліаденілювання; обмірковано зв'язок між поліаденілюванням та процесами транскрипції і сплайсингу; наведено приклади регулювання реакції утворення З'-кінців мРНК. In this review the contemporary understanding of a process of the 3'-end formation of vertebrates' mRNAs is summarized. The protein factors taking part in the reaction, and the signal sequences in pre-mRNAs guiding the process are characterized. The process of polyadenylation complex formation is analyzed. The relation between polyadenylation, on one hand, and transcription and splicing, on the other hand, is considered. The examples of the regulation of the polyadenylation reaction are given. The author proposes more strict definition of downstream signal than that available in literature.